Time-updated resting heart rate predicts mortality in patients with COPD - Omlor, Albert Joachim; Trudzinski, Franziska; Alqudrah, Mohamad; Seiler, Frederik; Biertz, Frank; Vogelmeier, Claus F.; Welte, Tobias; Watz, Henrik; Waschki, Benjamin; Brinker, Titus Josef; Andreas, Stefan; Fähndrich, Sebastian Wolfgang; et al. (Clinical research in cardiology, 2020)
High resting heart rate (RHR) is associated with higher mortality in the general population and in cardiovascular disease. Less is known about the association of RHR with outcome in chronic obstructive pulmonary disease (COPD). In particular, the time-updated RHR (most recent value before the event) appears informative. This is the first study to investigate the association of time-updated RHR with mortality in COPD. We compared the baseline and time-updated RHR related to survival in 2218 COPD patients of the German COSYCONET cohort (COPD and Systemic Consequences—Comorbidities Network). Patients with a baseline RHR > 72 beats per minute (bmp) had a significantly (p = 0.049) higher all-cause mortality risk (adjusted hazard ratio (HR) of 1.37 (1.00-1.87) compared to baseline RHR ≤ 72 bpm. The time-updated RHR > 72 bpm was markedly superior (HR 1.79, 1.30-2.46, p = 0.001). Both, increased baseline and time-updated RHR, were independently associated with low FEV1, low TLCO, a history of diabetes, and medication with short-acting beta agonists (SABAs). In conclusion, increased time-updated RHR is associated with higher mortality in COPD independent of other predictors and superior to baseline RHR. Increased RHR is linked to lung function, comorbidities and medication. Whether RHR is an effective treatment target in COPD, needs to be proven in controlled trials.
Gesehen am 01.10.2020